2020
DOI: 10.3354/dao03478
|View full text |Cite
|
Sign up to set email alerts
|

Marine mammals are natural hosts of Oceanivirga salmonicida, a bacterial pathogen of Atlantic salmon

Abstract: During 1992 and 1993, a bacterial disease occurred in a seawater Atlantic salmon Salmo salar farm, causing serious mortalities. The causative agent was subsequently named as Oceanivirga salmonicida, a member of the Leptotrichiaceae. Searches of 16S rRNA gene sequence databases have shown sequence similarities between O. salmonicida and uncultured bacterial clones from the digestive tracts of marine mammals. In the current study, oral samples were taken from stranded dolphins (common dolphin Delphinus delphis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…At the level of genus (Figure S2B), the gingival microbiota was composed primarily of Oceanivirga (15.6%), Neisseria (10.0%) and Ornithobacterium (10.0%), all undetected at the other facility sample sites, as well as Fusobacterium (11.6%) (Table S3). Oceanivirga , also unique to the gingival microbiota, has previously been isolated from the oral cavity of adult elephant seals at the same facility (Volokhov et al, 2018) and healthy wild harbour seals (Palmer et al, 2020). In the rectal microbiota, Bacteroidetes was also the most abundant (32.3%) phylum, followed by Proteobacteria (29.2%), Fusobacteriota (16.8%), Firmicutes (16.5%), Epsilonbacteraeota (2.6%) and Actinobacteria (2.5%).…”
Section: Resultsmentioning
confidence: 99%
“…At the level of genus (Figure S2B), the gingival microbiota was composed primarily of Oceanivirga (15.6%), Neisseria (10.0%) and Ornithobacterium (10.0%), all undetected at the other facility sample sites, as well as Fusobacterium (11.6%) (Table S3). Oceanivirga , also unique to the gingival microbiota, has previously been isolated from the oral cavity of adult elephant seals at the same facility (Volokhov et al, 2018) and healthy wild harbour seals (Palmer et al, 2020). In the rectal microbiota, Bacteroidetes was also the most abundant (32.3%) phylum, followed by Proteobacteria (29.2%), Fusobacteriota (16.8%), Firmicutes (16.5%), Epsilonbacteraeota (2.6%) and Actinobacteria (2.5%).…”
Section: Resultsmentioning
confidence: 99%
“…Identifying and quantifying sustained presence of pathogenassociated taxa is complicated; many animals regularly coexist with pathogenic microbiota without showing clinical signs of an affected health assessment (Nelson et al, 2015;Palmer et al, 2020). In some marine mammals, the conserved presence of disease-associated microbes like some Vibrio species and Helicobacter pylori among different populations can exist as a background "pathogen core community" (Apprill et al, 2017;Godoy-Vitorino et al, 2017;Raverty et al, 2017;Li et al, 2019) that is found in the majority of healthy populations (Nelson et al, 2015;Apprill et al, 2017;Ochoa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The genus Oceanivirga appeared mostly in the goat ejaculates collected during the breeding season and has also been detected in mare vagina (43,44) and bull semen (14). This genus belongs to the Leptotrichiaceae family, which typically colonizes human or animal oropharynx, respiratory, urogenital, and gastrointestinal tracts (45,46). The importance that these genera may have for reproductive performance remains unknown.…”
Section: Discussionmentioning
confidence: 99%